Invariant Processing of Multifrequency Signals - D. I. Popov (Известия высших учебных заведений России: Радиоэлектроника, 2015)
The multifrequency signal processing algorithm that is invariant to the values of Doppler phase components of multifrequency signals have been synthesized. The analysis of the detection characteristics of the respective system conducted that allows to determine the theoretical limit of improvement of real systems of this class, and the direction of the search for new systems.